A contribution to the rational design of Ru(CO)3Cl2L complexes for in vivo delivery of CO. Issue 11 (27th November 2014) - Seixas, João D.; Santos, Marino F. A.; Mukhopadhyay, Abhik; Coelho, Ana C.; Reis, Patrícia M.; Veiros, Luís F.; Marques, Ana R.; Penacho, Nuno; Gonçalves, Ana M. L.; Romão, Maria J.; Bernardes, Gonçalo J. L.; Santos-Silva, Teresa; et al.
Abstract : Water–gas shift chemistry modulates aqueous stability and protein interactions of Ru(CO)3 Cl2 L CORMs. Abstract : A few ruthenium based metal carbonyl complexes, e.g. CORM-2 and CORM-3, have therapeutic activity attributed to their ability to deliver CO to biological targets. In this work, a series of related complexes with the formula [Ru(CO)3 Cl2 L] (L = DMSO (3 ), l -H3 CSO(CH2 )2 CH(NH2 )CO2 H) (6a );d, l -H3 CSO(CH2 )2 CH(NH2 )CO2 H (6b ); 3-NC5 H4 (CH2 )2 SO3 Na (7 ); 4-NC5 H4 (CH2 )2 SO3 Na (8 ); PTA (9 ); DAPTA (10 ); H3 CS(CH2 )2 CH(OH)CO2 H (11 ); CNCMe2 CO2 Me (12 ); CNCMeEtCO2 Me (13 ); CN( c -C3 H4 )CO2 Et) (14 )) were designed, synthesized and studied. The effects of L on their stability, CO release profile, cytotoxicity and anti-inflammatory properties are described. The stability in aqueous solution depends on the nature of L as shown using HPLC and LC-MS studies. The isocyanide derivatives are the least stable complexes, and the S-bound methionine oxide derivative is the more stable one. The complexes do not release CO gas to the headspace, but release CO2 instead. X-ray diffraction of crystals of the model protein Hen Egg White Lysozyme soaked with6b (; Web:4UWN ) and8 (; Web:4UWV ) shows the addition of Ru II (CO)(H2 O)4 at the His15 binding site. Soakings with7 (; Web:4UWU ) produced the metallacarboxylate [Ru(COOH)(CO)(H2 O)3 ] + bound to the His15 site. The aqueous chemistry of these complexes is governed by the water–gas shift reaction initiated with the nucleophilic attack of HO − on coordinated CO. DFT calculations show this addition to be essentially barrierless. The complexes have low cytotoxicity and low hemolytic indices. Following i.v. administration of CORM-3, the in vivo bio-distribution of CO differs from that obtained with CO inhalation or with heme oxygenase stimulation. A mechanism for CO transport and delivery from these complexes is proposed.